Alat Bantu Penggerindaan Slideways Mesin Bubut - Fajar Aswin; Nanda Pranandita; Ary Kiswanto; Syahdan Hafiz; Zaenal Zaenal (Politeknik Manufaktur Negeri Bangka Belitung, 2017)
Lathe is a tool that rotates the work-piece about an axis of rotation to perform various operations such as cutting, sanding, knurling, drilling, or deformation, facing, turning, with tools that are applied to the work-piece to create an object with symmetry about that axis. There are several considerations that affect the lathe to work well, especially geometrical deviations that affect the quality degradation of the product in terms of shape and dimensions. One of the wear on the slide-way of the lathe can affect geometric aberrations. This paper discusses the design and manufacture of grinding tools to fix the lathes bed that can erode three slide-way planes in a single process to achieve flatness and square alignment with one another. The research method used is the experimental method by collecting the data needed to design the tool through literature study and direct observation to the lathe, then the data is processed to obtain the specification of the tool that will be designed by design method based on Verien Deutche Ingenieuer (VDI) 222 , the design result is then continued with the machining and fabrication process; before assembling, parts of the auxiliary equipment are tested in accordance with the design function indicator; the last stage is testing the tool as a whole to know the achievement of the tool against a predetermined goal. Based on the results of the grinding experiment on the three slideway planes with a feed depth of 0.03mm, the average flatness and alignment values ??are 0.02mm / 300mm and 0.07mm / 300mm, respectively. Based on the ISO 1708 standard on the tolerance of geometrical deviations, the grinding results have not allowed the tolerance. Still need more research about the influence of wear of grinding wheels to the grinding results.